Virtual Lab Development to Enhance Student Learning: A Quality Circle Approach - Pandey, Amarjeet S; Kalkhambkar, Vaiju; Kumbhar, Sachin; Nathgosavi, Kiran; A., Sujil (Journal of Engineering Education Transformations, 2025)
The COVID-19 pandemic has affected the student fraternity to physically access the laboratory and conduct experiments offline. Across the world, new platforms have been designed with ICT tools for the smooth conduction of academics specifically for laboratory courses. This article aims to provide quality circle-based guidance to the community to develop a Virtual Laboratory. The virtual lab is developed through an emphasis on Quality Circle methodology. The Quality Circle team has developed an instructional methodology known as the virtual laboratory (VL). It incorporates pedagogical techniques that help students to better understand the theoretical concepts in an effective and joyful way.